Spontaneous mass transfer and deposition of carbon and silicon on titanium in LiCl-Li ionic-electronic melts - Anfinogenov A.I.; Martem’yanova Z.S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Coatings and powders containing separate phases of silicides and carbides have been obtained during the joint saturation of titanium by carbon and silicon in ionic-electronic melt Li- LiCl.